2021
DOI: 10.1103/physrevb.104.054413
|View full text |Cite
|
Sign up to set email alerts
|

Penetration depth of Cooper pairs in the IrMn antiferromagnet

Abstract: Suppression of superconductivity due to the proximity effect between a superconductor and a ferromagnet can be partially alleviated when a Cooper pair simultaneously samples different directions of the short-range exchange field. The superconductor's critical temperature, T C , is therefore expected to partially recover when the ferromagnet is in a multidomain state, as opposed to a single-domain state. Here, we discuss series of experiments performed with ferromagnet(Pt/Co)/spacer(IrMn and Pt)/superconductor(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, employing the two-sublattice quasiclassical Green's functions theory developed, our analysis reveals the effect of disorder on all these mechanisms. This seemingly complete picture allows us to envisage the various competing effects taking place in a realistic AF/S bilayer [19,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, employing the two-sublattice quasiclassical Green's functions theory developed, our analysis reveals the effect of disorder on all these mechanisms. This seemingly complete picture allows us to envisage the various competing effects taking place in a realistic AF/S bilayer [19,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments have found that AFs lower the critical temperature of an S layer [19,[22][23][24], despite the no net spin-splitting argument above. In some cases, the effect has been comparable to or even larger than that induced by a ferromagnet layer [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation